If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5X + -7) + (4X + 11) = 14 + -1X Reorder the terms: (-7 + 5X) + (4X + 11) = 14 + -1X Remove parenthesis around (-7 + 5X) -7 + 5X + (4X + 11) = 14 + -1X Reorder the terms: -7 + 5X + (11 + 4X) = 14 + -1X Remove parenthesis around (11 + 4X) -7 + 5X + 11 + 4X = 14 + -1X Reorder the terms: -7 + 11 + 5X + 4X = 14 + -1X Combine like terms: -7 + 11 = 4 4 + 5X + 4X = 14 + -1X Combine like terms: 5X + 4X = 9X 4 + 9X = 14 + -1X Solving 4 + 9X = 14 + -1X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add 'X' to each side of the equation. 4 + 9X + X = 14 + -1X + X Combine like terms: 9X + X = 10X 4 + 10X = 14 + -1X + X Combine like terms: -1X + X = 0 4 + 10X = 14 + 0 4 + 10X = 14 Add '-4' to each side of the equation. 4 + -4 + 10X = 14 + -4 Combine like terms: 4 + -4 = 0 0 + 10X = 14 + -4 10X = 14 + -4 Combine like terms: 14 + -4 = 10 10X = 10 Divide each side by '10'. X = 1 Simplifying X = 1
| 5x=4x-1 | | x^2-7x=20 | | x^2-7x-20=-200 | | x^2-7x-20=0 | | 81-6x=10x-5x | | 5x^2+8x+42=0 | | 6x+33=16x-67 | | 12+1.5a=2a | | 5(x-6)-6(x-5)=x+2-(x-3) | | 12n-24=14n+28 | | x^3+x^2=25 | | 7(1-s)=-2(5s+4)+6s | | 3n+11=-16 | | 4y-9=18y+5 | | 2f-6=75+24 | | 10x+10=8x+2 | | 4(2-x)-3(7x+5)+6(3x-1)=2(8-x) | | 8x+9=5x+30 | | 3(x-2)-4(2x-3)=2(3x-1)-3(3x+1)+3 | | 3(2-3x)-2(5x-1)-3-2x=0 | | x-2(x-3)=5x+3(2x+2) | | 9x+24=5x+120 | | 5(3-x)-3(5-x)=0 | | -11=11(c-3) | | 99-5x=31x+15 | | 265-6x=39x+15 | | x^3+7x^2+200=0 | | 6(x-5)=-30 | | 15x=3(x-1)-4(1-x) | | -3=3(x+6) | | 149-5x=22x+23 | | 5x+13=-137-10x |